OBSTRUCTIVE JAUNDICE: CURRENT PRINCIPLES OF DIAGNOSIS AND TREATMENT - VALERIY I. Podoluzhnyi (Фундаментальная и клиническая медицина, 2018)
Here I briefly review anatomy and physiology of bile system, epidemiology, classification, development, signs and symptoms, diagnosis, and treatment of cholestasis and obstructive jaundice. Among the causes of obstructive jaundice, cholestasis-induced benign diseases have the highest prevalence (80%) and are followed by malignant tumors, mainly pancreatic cancer. Bile hypertension entails movement of the bile components to lymph and blood increasing level of bilirubin, cholesterol, and bile acids. Restriction or termination of the release of bile into the duodenum disturbs the digestion of fats with the further development of steatorrhea. Stagnant bile disrupts enterohepatic circulation and activates lipid peroxidation ultimately resulting in a significant hepatotoxicity. A number of cell death subroutines provoke inflammation and liver fibrosis. Cholelithiasis is also associated with the development of cholangitis. Early diagnosis of obstructive jaundice requires non-invasive examination (blood test, ultrasonography, magnetic resonance cholangiography, and computed tomography) and can demand invasive methods to evaluate biliary tract patency (endoscopic retrograde cholangiopancreatography and percutaneous transhepatic cholangiography). Surgical treatment of cholestasis includes intitial transpapillary or percutaneous biliary decompression with the following invasive intervention. Surgery should be accompanied by hepatoprotective therapy; in severe cases, plasmapheresis or liver dialysis are expedient.